Analisa Kinerja System Gluster FS pada Proxmox VE untuk Menyediakan High Availability - Lalu Zazuli Azhar Mardedi; Ariyanto Ariyanto (Universitas Bumigora, 2019)
Virtualization is used as a means to improve the scalability of existing hardware. Proxmox Virtual Environment (PVE) with hypervisor type based on open source. PVE can use Network Attached Storage as a network-based storage location in GlusterFS storage, which is a distributed file system. The research methodology uses Network Development Live Cycle (NDLC) which has 3 (three) stages, namely analysis, design, and simulation prototyping. The analysis phase is carried out by collecting data by means of literature study and data analysis. The design phase is carried out making the design of network systems and trials. At the simulation stage prototyping tests various scenarios and analyzes Read, Write and Re-Write tests. The system in PVE is integrated with GlusterFS storage made using two servers including the PVE 1 and PVE 2 servers. GlusterFS performance results show that the Read file capability is higher compared to Write, and Re-write in the measurement variations of 1mb, 10mb and 100mb files. In conclusion, GlusterFS can be clustered using the same node as PVE Cluster which can use GlusterFS as additional storage for PVE. GlusterFS also supports live migration features so that LXC or VM can do live migration from one node to another in an online state. The ability to write, re-write and read files on GlusterFS is also relatively stable in testing file size variations.